Do functional impairments promote or hinder mental health treatment seeking: Differential results for women and men. (January 2019) - Vogt, Dawne; Danitz, Sara B.; Fox, Annie B.; Sanders, Wesley; Smith, Brian N.
Highlights: It is not known whether functional impairment facilitate or hinder treatment seeking. Research has yet to examine whether functional impairment operates differently for women and men. The current study addressed this research question among post-9/11 veterans. Findings suggest that relationship impairment, but not work impairment, interferes with treatment seeking for men but facilitates treatment seeking for women. Results highlight the potential value of gender-informed approaches to treatment promotion. Abstract: Although symptom severity is a known predictor of treatment seeking, the role of functional impairment in this association is unclear. The purpose of this study was to examine the contribution of relationship and work impairment to service use among women and men with posttraumatic stress disorder (PTSD) and depression symptoms. Data from mailed surveys of 363 military veterans were examined longitudinally. Stratified regression analyses were applied to evaluate moderating and mediating effects of functional impairment in association between symptoms and mental health service use, with significant effects observed for relationship but not work impairment. For men, relationship impairment moderated the association between mental health and service use, such that the impact of depression symptoms on treatment seeking was reduced when accompanied by high impairment. For women, subsequently assessed relationship impairment acted as a mediator of the positive association between PTSD symptom severity and service use. The finding that relationship impairment interfered with treatment seeking for men but facilitated treatment seeking for women may help explain widely demonstrated sex differences in treatment seeking. Results underscore the importance of attending to the role of relationship impairment in veterans' treatment seeking and highlight the value of implementing sex-informed approaches to treatment promotion efforts.